BIOACTIVE COMPOUNDS FROM INDONESIAN ERYTHRINA (LEGUMINOSAE) - , Tati Herlina, Unang Supratman, Ukun M.S. Soedjanaatmadja, Anas S ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
Traditional medicines originating from plants have been widely used as an alternative theraphy and extensive research have identified several bioactive compounds of the plants. In Indonesia, Erythrina (Leguminosae) plants have been used for medication to many diseases including anthelmintic, malaria, and antifertility. In the course of our continuing search for novel bioactive compounds from Indonesian Erythrina plants, we isolated and described several bioactive compounds such as paralytic alkaloids